Análise da cobertura das linhas e dos pontos de ônibus da cidade de São Carlos-SP - Sabbadin, Ana Carolina (Universidade Federal de São Carlos, 2021)
This work purpose to verify the coverage area and the population served by the lines and bus stops, as well as highlight the importance of quality public transport in the development of a city and in the population's quality of life. For that, the object of study is the public transport system of the city of São Carlos, composed of its bus lines and its bus stops. The efficiency in coverage of this service, which is the responsibility of the Suzantur company, was analyzed. The analysis was carried out by crossing population information by sector of the city and coverage of lines and bus stops, making it possible to verify the efficiency of public transport in the city, as well as to compare the data obtained by analyzing the method that evaluates the coverage area of the bus lines and the method that assesses the coverage area of the stopping points. For this, quality references presented by Ferraz and Torres (2004) were used. For the development, the QGIS program was used, for the treatment of georeferenced information, as well as population data by sector obtained by the IBGE. After the analysis, it was possible to observe that both methods serve more than 90% of the population in urbanized areas. However, to measure the total quality of public transport, additional work is needed to check other important issues about the quality of this system and thus make this means more attractive, given its benefits for society and for the user. In addition, more up-to-date data is needed, as the bus stops file was found to have deactivated stops that are still mapped.
Lines and bus stops coverage analysis in São Carlos-SP city
Keywords: Transporte público; Transporte coletivo; Linhas de ônibus; Pontos de parada; Cobertura; Public transport; Bus lines; Bus stops; Coverage; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES::PLANEJAMENTO E ORGANIZACAO DO SISTEMA DE TRANSPORTE